Acúmulo e exportação de nutrientes em cenoura 'Forto' - Cecílio Filho, Arthur Bernardes [UNESP]; Peixoto, Fabrício de Carvalho [UNESP] (My University, 2013)
In order to quantify the growth, accumulation and exportation of macronutrients by carrot 'Forto', and obtain equations that best represent them, it was conducted an experiment in the São Gotardo (MG), from May to September 2004. Samples were taken at 40, 50, 60, 70, 80, 90, 100, 110 and 120 days after sowing (DAS) to determine dry matter and accumulation of macronutrients in leaves and roots. At 40 DAS, five days after thinning, the plants had 0.18 g and 0.04 g in dry leaves (LDM) and of roots (RDM), respectively. From then, until 88 DAS, the partitioning of photoassimilates and accumulation of matter in the shoots were more pronounced. The RDM was low until 80 DAS, which corresponded to two thirds of the crop cycle, from when the amount of material allocated in this part of the plant had strong growth, surpassing, at 88 DAS, the amount of LDM. The nutrient accumulation was small in the first 60 DAS, coinciding with the period of lower dry matter accumulation. The order of decreasing macronutrient accumulation by the crop were: K > N > Ca > P > S > Mg, in the amounts of 906.7, 438, 155.46, 87.4, 58 and 37.63 mg plant-1, respectively. The root participated with 60.5% of the accumulation of N, 86.1% of P, 58% of K, 25.5% of Ca, 55.6% of Mg and 65.5% of S. Considering a population of 590,000 plants per hectare, the total quantity of nutrients by the crop of carrots was 258.3, 51.6, 534.8, 91.7, 22.2 and 34.2 kg N ha-1, P, K, Ca, Mg and S, respectively.

Com o objetivo de quantificar o crescimento, o acúmulo e a exportação de macronutrientes pela cenoura ‘Forto’, e obter equações que melhores os representem, conduziu-se um experimento em São Gotardo (MG), de maio a setembro de 2004. As amostragens de plantas foram realizadas aos 40, 50, 60, 70, 80, 90, 100, 110 e 120 dias após a semeadura (DAS), para determinação da matéria seca e do acúmulo dos macronutrientes em folhas e raízes. Aos 40 DAS, cinco dias após o desbaste, as plantas apresentavam 0,18 g e 0,04 g em matéria seca de folhas (MSF) e de raiz (MSR), respectivamente. A partir de então, até 88 DAS, a partição de fotoassimilados e acúmulo de matéria, na parte aérea, foram mais acentuados. A MSR foi pequena até 80 DAS, o que correspondeu a dois terços do ciclo cultural, a partir de quando a quantidade de matéria alocada nesta parte da planta teve forte incremento, ultrapassando, aos 88 DAS, a quantidade de MSF. O acúmulo de nutrientes foi pequeno nos primeiros 60 DAS, coincidindo com o período de menor acúmulo de matéria seca. A ordem decrescente do macronutrientes acumulados pela cultura foi: K > N > Ca > P > S > Mg, nas quantidades de 906,7; 438; 155,46; 87,4; 58 e 37,63 mg planta-1, respectivamente. A raiz participou com 60,5% do acúmulo de N; 86,1% de P; 58% de K; 25,5% de Ca; 55,6% de Mg e 65,5% de S. Considerando uma população de 590.000 plantas por hectare, a quantidade acumulada dos nutrientes pela cultura da cenoura foi de 258,3; 51,6; 534,8; 91,7; 22,2 e 34,2 kg ha-1 de N, P, K, Ca, Mg e S, respectivamente.
Accumulation and exportation of nutrients by carrot 'Forto'
Keywords: Daucus carota L.; Growth; Nutrient uptake